The literate and non-literate subject in Central do Brasil: scenes of orality and literacy (Research, Society and Development, 2019)
Central Brazil, the 1998, brazilian film winner Walter Salles, brings the illustrious Brazil and its social and ideological implications to the lenses of the big screen - the cinema - the 3 x 4 portrait of an illiterate Brazil and its social and ideological implications. From this point of view, this bibliographic study, of a qualitative nature, aims to reflect on the presence of social literacy practices, built through the discourse of literate subjects, although not literate, portrayed in the film. The analysis demonstrates that the processes of reading, writing and orality are inseparable instances in today's literate society, built on the aegis of grafocentrism, that is, increasingly focused on reading and writing, with meaning and significance in their interaction territories social.